Effects of modified tall oil versus conjugated linoleic acid on finishing pig growth performance and carcass characteristics - OQuinn, P.R.; Smith, J.W.II; Tokach, Michael D.; Smith, J. Scott; Nelssen, Jim L.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A growth trial was conducted to compare effects of modified tall oil (MTO) and conjugated linoleic acid (CLA) on growth performance, serum chemistry, and carcass composition of finishing barrows. Overall, pigs fed the control diet did not differ from pigs fed MTO or CLA supplemented diets. However, pigs fed MTO had greater ADG and ADFI than pigs fed CLA. No effect of treatment was observed for any of the measured carcass criteria or serum triglyceride levels. The results of this research do not suggest a benefit from feeding MTO or CLA to pigs but do indicate differences in ADG and ADFI that favor those fed MTO.
Keywords: Swine; Modified tall oil; Conjugated linoleic acid; Growth; Carcass